Synergistic effects of climate and land use on avian beta‐diversity. Issue 11 (16th August 2017) - Ferger, Stefan W.; Peters, Marcell K.; Appelhans, Tim; Detsch, Florian; Hemp, Andreas; Nauss, Thomas; Otte, Insa; Böhning‐Gaese, Katrin; Schleuning, Matthias
Abstract: Aim: Gradients in climate and land use occur simultaneously in many of the Earth's ecosystems and thus collectively impact most ecological communities. Albeit climate and land use have potentially interacting effects on ecological communities that may exacerbate or ameliorate their individual effects, little is known about the effect of the climate–land use interaction on community composition. A better understanding of the interaction between climate and land use is essential to predict the impacts of environmental change on ecological communities. Location: Mt. Kilimanjaro, Tanzania. Methods: We quantified the community composition of bird species and feeding guilds on 64 study plots of 13 different habitat types along an elevational gradient from 870 to 4550 m a.s.l. We partitioned the variation in pairwise beta‐diversity (βcc ) of birds and its two additive components, abundance differences (βabu ) and replacement (β−3 ), among the effects of temperature, land‐use intensity and their interaction. Results: Temperature and land use had synergistic effects on beta‐diversity (βcc ) of birds; that is, the combination of high temperature and high land‐use intensity led to higher beta‐diversity than expected from the sum of both individual effects. While temperature explained more of the variation in abundance differences (βabu ), land use explained more of the variation in the replacement of individuals between species and feeding guilds (β−3 ), indicating that different processes drove avian beta‐diversity along the temperature and land‐use gradients. Main Conclusions: Our results challenge previous studies that investigated the effects of climate and land use in isolation because disregarding their synergistic interaction underestimates the joint effect of climate and land use on biodiversity. A consideration of the synergy between climate and land use is essential for adequate predictions of the impact of global change on biodiversity.